Estratégia de produção e gestão de suprimentos: estudo de casos no setor de linha branca - Calife, Naiara Faiad Sebba (Universidade Federal de São Carlos, 2008)
The growing pressure for competitiveness and development of flexible production systems enhanced the strategic role of the production to achieve the goals of global enterprises. The decisions on production should be integrated with strategic decisions of the organization, and the organizational functions of production support stop being performed individually, and also take over strategic role in corporations, it is, for instance, the case of supplies function. This study aims to identify and analyze the Production Strategies and Supplies Management in two important companies in the white line area and check out if and how the function Supplies influences and is influenced by these strategies. The white line area has experienced, since the last decade, intense process of internationalization of production and concentration of capital. Such processes accelerated the diffusion rhythm of innovations in this sector, causing changes in the management and production organization. Furthermore, the existence of a gap in the theory that relates Production Strategy and Supplies Management makes us to bring this relation into practice. One opted for an approach of qualitative and exploratory character, and the research strategy used was the case study. It was possible to check the relevance of these issues for the companies studied so that they could achieve a favorable competitive position, and it was noticed that the priorities of the area of supplies are aligned with the competitive priorities of the enterprises, showing that the supplies management acts by giving support to the production strategy and vice-versa.
Production Strategy and Supply Management: cases study in the white line sector
Keywords: Estratégia de produção; Gestão de suprimentos; Indústria de linha branca; Production strategy; Supply management; White line; ENGENHARIAS::ENGENHARIA DE PRODUCAO